What is the best treatment for nocturnal enuresis in children?. Issue 3 (March 2016) - Fieldsted, Tyler; Daly, Sarah
Abstract : Evidence‐Based Answer : The enuresis alarm reduces nighttime bed‐wetting in about two‐thirds of children during treatment; half of children will remain dry after the alarm is discontinued. Desmopressin results in fewer wet nights while on treatment; however, almost all children start bedwetting again when treatment is stopped. Combining desmopressin and alarm use does not result in better cure rates after the end of treatment (SOR: A, systematic reviews).